Hydroxyapatite production from animal bone sources - Nguyễn, Phước Nhân; Hồ, Văn Thành; Trần, Thanh Minh; Nguyễn, Ngọc Uyên Thư; Lê, Trung Hiếu; Lê, Lâm Sơn; Lê, Thị Hòa (Hue University Journal of Science: Natural Science, 2025)
In this study, the bone char composition of cows, buffaloes, pigs, and goats was studied. The samples were characterized by using X-ray diffraction, thermal analysis, scanning electron microscopy, and energy-dispersive X-ray spectroscopy. The main component is hydroxylapatite (Ca5(OH)(PO4)3) with the following content: 67.7% in buffalo bones, 65.2% in cow bones, 58% in pig bones, and 48% in goat bones. The bone char exhibits a nano-sized morphology ranging from fibres to granules depending on the calcination temperature and animal bone type. The bone char is suitable as a starting material for producing organic nano phosphate fertilizer.